Epidemiological survey - Boelee, Eline; Laamrani, Hammou (2009)
This tool uses standard biomedical methodologies to determine infection rates for key water-related (or “reservoir-related”) diseases including schistosomiasis and other intestinal parasites, and malaria. In any particular locale there may be a completely different set of priorities with regard to reservoir-related health issues. Therefore, it is always wise to check with local health personnel about priorities, and to sample local communities’ perceptions with respect to reservoir-related problems. For diseases and infections not described in this tool, local health professionals, literature, and the internet provide good starting points.